Linking life history strategies and historical baseline information shows effects of altered flow regimes and impoundments on freshwater mussel assemblages. (13th July 2020) - Khan, Jennifer M.; Dudding, Jack; Hart, Michael; Tsakiris, Eric; Randklev, Charles R.
Abstract: Human impacts on aquatic ecosystems are causing shifts in the composition and distribution of species, leading to subsequent changes in community structure. However, these changes may not be fully realised because of inadequate baseline information. In Texas, such baseline information is generally lacking for cryptic aquatic species such as unionid mussels, which will be likely to impede identification of impacted populations, potential causal factors, and the setting or achieving of management goals. The Navasota River, located in central Texas, is an exception, having been comprehensively surveyed more than 40 years ago, prior to large‐scale impoundment of this system. Hierarchical cluster analysis, nonmetric multidimensional scaling, and fuzzy set ordination were performed to compare assemblage structure from the 1975 survey to that of a recent survey in 2016 at similar sampling locations. Comparing sites based on the presence–absence of mussel species, we found no significant differences between the number of taxa and species present; however, we did find significant filtering of mussel life history strategies. Specifically, prior to impoundment, we found that mussel assemblages were filtered based on longitudinal patterns in life history strategy from taxa that are adapted to disturbed habitats to those favoured in more stable habitats with low environmental variation. However, following large‐scale impoundment after 1975, we saw a shift in the hydrologic regime towards consistent, homogenised flows and a shift in assemblage structure towards equilibrium species. This shift appears to represent a discontinuity, wherein river impoundment alters physical parameters of the hydrologic regime and these changes in turn modify biotic patterns and processes. Our results provide another example of how large dams can restructure mussel assemblages, highlight the importance of incorporating reference or baseline conditions wherever possible when evaluating the conservation status of aquatic biota, and provide further evidence for the use of life history theory and the serial discontinuity concept in predicting the consequences of flow alteration and river impoundment.